Socioeconomic factors associated with low birth weight in the Andean region of Peru - Betancur, Heber Nehemias Chui; Llanos, Madelein Stefanny Callohuanca; Argollo, Katia Pérez; Ávalos, Edgar Darío Callohuanca; Sánchez, Lily Maribel Trigos; Monrroy, Dante Elmer Hancco; Huanca, Bernardo Roque (O Mundo da Saúde, 2024)
Over 20 million newborns worldwide are born with low birth weight (LBW), prompting the WHO to establish a target of a 30% reduction by 2025. To achieve this goal, developing countries must implement effective policies to address contributing factors. This study aimed to identify the socioeconomic factors associated with low birth weight (LBW) in the Peruvian Andes, a region characterized by monetary poverty. A quantitative approach with an explanatory design was adopted, utilizing 2,408 records of women with singleton deliveries, assessed from the 22nd week of pregnancy with fetuses weighing ≥500 g, through term delivery, along with their newborns (NB) at the Regional Hospital of Ayacucho, Peru. The odds of socioeconomic factors associated with low birth weight (LBW) were evaluated using odds ratio and Pearson’s Chi-Square test, with a p-value <0.01. The results of this study indicate that mothers with Grade II and Grade I anemia had a 3.45-fold and 1.89-fold increased risk, respectively, of delivering newborns with low birth weight (LBW) (95% CI; p < 0.05). Another significant factor was a household income below 1,000.00 soles (<268 USD/month), which was associated with a 3.59-fold increased risk of having a newborn with LBW (95% CI: 1.58–5.51; p < 0.05).